All that glitters is not always gold. (10th February 2014) - Harrison, E; Hayes, S; Howell, L; Lal, S
Abstract : Biopsies from the second part of the duodenum are routinely performed in patients with unintentional weight loss. When villous atrophy and an increased intraepithelial lymphocytosis are detected, the commonest cause of it is coeliac disease. Severe villous atrophy with increased intraepithelial lymphocytosis (Marsh IIIc) is highly specific for coeliac disease. However, coeliac disease with this presentation is very rare. Milder abnormalities such as Marsh I-II (microscopic enteritis) and Marsh IIIa are not specific for coeliac disease and could occur in other conditions like those listed in the discussion. We present the case of a 74-year-old woman who, after being diagnosed with seronegative coeliac disease, failed to improve on a gluten-free diet. We discuss the differential diagnosis of coeliac disease and the possible alternative causes for villous blunting, paying particular attention to the diagnosis of small intestinal bacterial overgrowth.